Composite, hydrogenation catalyst and preparation method thereof

By adopting a composite structure with different metal elements in the hydroxide reaction catalyst, using the hydrogen storage capacity of the Pd layer and the catalytic activity of the Ru layer, the problem of Ru inactivation in the HOR potential interval is solved, and a higher under high potential is achieved Catalytic activity and efficient hydrogen storage and release.

CN115117369BActive Publication Date: 2025-02-25TAN KAH KEE INNOVATION LAB
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210907773.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-29
Publication Date
2025-02-25
Estimated Expiration
2042-07-29

AI Technical Summary

Technical Problem

Metal Ru is inactivated by oxygen-permeability within the hydroxide reaction (HOR) potential range, resulting in insufficient catalytic activity of anion exchange membrane fuel cell.

Method used

A composite is employed, the composite comprises a substrate, a first cover layer and a second cover layer. The matrix contains a metal element whose radius is greater than Pd, the first cover layer contains a Pd element, and the second cover layer contains a Ru element with catalytic activity of the hydroxide reaction. With this structure, the Pd layer can store hydrogen and release activated hydrogen when the Ru layer is occupied by oxygen-containing species, ensuring the continuous progress of the HOR reaction.

Benefits of technology

The complex still maintains high catalytic activity under high potential, solving the problem that Ru is easily toxic to oxygen-containing species in the HOR potential interval, and improves the storage and release performance of the catalyst by controlling the thickness of the Pd layer. The energy barrier of the Volmer step is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115117369B_ABST
    Figure CN115117369B_ABST
Patent Text Reader

Abstract

The present invention relates to a composite body, a hydrogen oxidation catalyst and a preparation method thereof. The composite body comprises: a substrate, the substrate contains a first element, the first element is selected from at least one metal element with a metal radius greater than Pd; a first covering layer, the first covering layer covers at least a part of the surface of the substrate, the first covering layer contains the Pd element; a second covering layer, the second covering layer covers at least a part of the surface of the first covering layer, and the second covering layer contains a substance having a catalytic activity for hydrogen oxidation reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, and in particular to a composite, a hydrogen oxidation catalyst and a preparation method thereof. Background Art

[0002] Hydrogen fuel cells are a sustainable green energy conversion technology that converts chemical energy into electrical energy. Hydrogen oxidation reaction (HOR), a basic reaction of anion exchange membrane fuel cells (AEMFCs), is kinetically limited to the Volmer step under alkaline conditions: MH ad +OH - →M+H2O+e - .

[0003] Metallic Pt has been considered the most ideal catalyst material due to its moderate hydrogen binding energy, but its high price has always been a cost issue that has hindered the development of anion exchange membrane fuel cells. Therefore, the development of low-cost, highly active non-platinum anode catalysts has always been a key need for the further commercialization of AEMFCs.

[0004] Ru has similar properties to Pt, but is much cheaper, making it a potential alternative to platinum-based catalysts. Similar to early transition metals, Ru has a higher affinity for oxygen than Pt, which leads to the preferential formation of Ru-OH at relatively low anodic potentials. ad The relevant theory holds that if a single active site on the catalyst surface is occupied by OH ad After occupation, H2 dissociation adsorption can no longer be carried out, which is also the essential reason for the insufficient activity of Ru in HOR. Summary of the invention

[0005] Solving the problem of metal Ru being deactivated due to its affinity for oxygen in the hydrogen oxidation reaction (HOR) potential range is of great significance for reducing the application cost of anion exchange membrane fuel cells. In response to the above problem, the present application proposes a new composite, which has unique properties different from those of metal Ru. Experiments show that even if a single active site of the composite is OH ad occupied, it can still complete the Volmer step alone.

[0006] In a first aspect, the present application provides a composite comprising:

[0007] A matrix, wherein the matrix contains a first element, wherein the first element is selected from at least one metal element having a metal radius greater than that of Pd;

[0008] A first covering layer, wherein the first covering layer covers at least a portion of the surface (e.g., the entire surface) of the substrate, and the first covering layer contains a Pd element;

[0009] The second covering layer covers at least a portion of the surface (eg, the entire surface) of the first covering layer, and the second covering layer contains a substance having a catalytic activity for hydrogen oxidation reaction (eg, Ru).

[0010] In the above scheme, the first covering layer containing Pd element can play the role of hydrogen storage. Based on this, when the surface active sites of the second covering layer are occupied by oxygen-containing species (OH ad , O ad When Pd (such as Pd) is adsorbed on the first covering layer, the first covering layer can release active hydrogen (hydrogen atoms) to the second covering layer, so that the HOR reaction can continue. In the above scheme, the metal radius in the substrate is larger than that of Pd, and there is a lattice mismatch between the first covering layer and the substrate. The lattice mismatch causes the first covering layer to be stretched by the substrate, and the stretching effect significantly improves the hydrogen storage capacity of the first covering layer, so that the active hydrogen (hydrogen atoms) can be stored in the first covering layer, and then overflow to participate in the reaction of oxygen-containing species adsorbed on the second covering layer, completing the Volmer step, thereby improving the HOR catalytic activity of the composite as a whole.

[0011] In some embodiments, the thickness of the first covering layer is 0.3nm-10nm, for example, 0.3nm-0.5nm, 0.5nm-1nm, 1nm-2nm, 2nm-3nm, 3nm-4nm, 4nm-5nm, 5nm-6nm, 6nm-7nm, 7nm-8nm, 8nm-9nm or 9nm-10nm. Based on the above scheme, the tensile stress from the substrate can fully act in the first covering layer of relatively thin thickness, so that the first covering layer is fully subjected to the tensile effect of the substrate. The thickness of the first covering layer is preferably 1.1nm-6.3nm, more preferably 1.1nm-3.5nm.

[0012] In some embodiments, the first element is selected from metals with a radius of The above elements, such as metal radius is or elements.

[0013] In some embodiments, the term "metallic radius" refers to half the distance between adjacent metal nuclei in a metal crystal lattice.

[0014] In some embodiments, the metal radius of an atom can refer to the following literature: Ge Xiutao, ed. Physical Chemistry [M]. Hefei: University of Science and Technology of China Press, 2019.09, pp. 454-460.

[0015] In some embodiments, the first element is selected from The metal radii of the above elements are shown in brackets.

[0016] In some embodiments, the substance having catalytic activity for hydrogen oxidation reaction is selected from a single substance, alloy or intermetallic compound containing the following elements: Mn, Ni, Co, Mo, Cu, Fe, Ir, Os, Pd, Pt, Rh or Ru. Based on the above scheme,

[0017] In some embodiments, the substance having catalytic activity for hydrogen oxidation reaction is selected from a single substance, an alloy or an intermetallic compound containing the following elements: Ir, Os, Pd, Pt, Rh or Ru.

[0018] In some embodiments, the second capping layer is a single substance, an alloy, or an intermetallic compound containing a platinum group metal.

[0019] In some embodiments, the second cover layer has a different composition than the first cover layer.

[0020] In some embodiments, the second capping layer is composed of Ru element, Ru alloy, Ru intermetallic compound or a combination thereof.

[0021] In some embodiments, the content of Ru element in the second covering layer is 10%-20%, 20%-30%, 30%-40%, 40%-50%, 50%-60%, 60%-70%, 70%-80%, 80%-90%, 90%-100%.

[0022] In some embodiments, the first capping layer comprises a Pd element, a Pd alloy, a Pd intermetallic compound, or a combination thereof.

[0023] In some embodiments, the content of Pd element in the first covering layer is 10%-20%, 20%-30%, 30%-40%, 40%-50%, 50%-60%, 60%-70%, 70%-80%, 80%-90%, 90%-100%.

[0024] In some embodiments, the material of the substrate may be a metal single substance or an alloy, the material of the first covering layer may be a metal single substance or an alloy, and the material of the second covering layer may be a metal single substance or an alloy.

[0025] In some embodiments, the first cover layer may be metal bonded to the substrate, and the second cover layer may be metal bonded to the first cover layer.

[0026] In some embodiments, the thickness of the second covering layer is 0.1nm-10nm, such as 0.1nm-0.5nm, 0.5nm-1nm, 1nm-2nm, 2nm-3nm, 3nm-4nm, 4nm-5nm, 5nm-6nm, 6nm-7nm, 7nm-8nm, 8nm-9nm or 9nm-10nm. The thinner the thickness of the second covering layer, the more conducive it is for activated hydrogen to pass through the second covering layer and enter the first covering layer for storage. The preferred thickness of the second covering layer is 0.1nm-1.0nm, such as 0.5nm-0.8nm.

[0027] In some embodiments, the matrix may be in the form of particles, threads, strips, films, or blocks.

[0028] In some embodiments, the complex may be in the form of granules, threads, ribbons, films, blocks, or a mixture thereof.

[0029] In some embodiments, the matrix has a size in at least one dimension of 10 nm to 100 nm.

[0030] In some embodiments, the matrix has a size in at least two mutually perpendicular dimensions of 10 nm to 100 nm.

[0031] In some embodiments, the size of the matrix in three mutually perpendicular dimensions is 10 nm to 100 nm.

[0032] In some embodiments, the matrix has a size in at least one dimension of 100 nm to 1000 nm.

[0033] In some embodiments, the size of the matrix in at least two mutually perpendicular dimensions is between 100 nm and 1000 nm.

[0034] In some embodiments, the size of the matrix in three mutually perpendicular dimensions is 100 nm to 1000 nm.

[0035] In some embodiments, the complex is a particle having a core-shell structure, wherein the particle comprises a core and a shell covering the core;

[0036] The core is the matrix;

[0037] The shell includes a first covering layer and a second covering layer;

[0038] The first covering layer covers the core;

[0039] The second covering layer covers the first covering layer.

[0040] In some embodiments, the first capping layer is epitaxially grown on the substrate.

[0041] In some embodiments, the second capping layer is epitaxially grown on the first capping layer.

[0042] In some embodiments, the substrate is completely covered by the first covering layer.

[0043] In some embodiments, the first coating layer is completely coated by the second coating layer.

[0044] The term "epitaxial growth" has the same meaning as "epitaxial formation" and "epitaxial deposition". It refers to the deposition / growth / formation of a covering layer on the surface of a substrate, and the covering layer has the same or similar crystal properties (such as crystal orientation) as the substrate surface. The epitaxial growth method can adopt the common methods in the art, such as vapor deposition, liquid phase growth, electrodeposition, chemical plating deposition, etc.

[0045] In a second aspect, the present application provides a method for preparing any of the above-mentioned complexes, comprising:

[0046] Providing a substrate, wherein the substrate contains a first element, wherein the first element is selected from at least one metal element having a metal radius greater than Pd;

[0047] forming a first covering layer on at least a portion of the surface of the substrate, wherein the first covering layer covers at least a portion of the surface of the substrate, and the first covering layer contains a Pd element;

[0048] A second covering layer is formed on at least a portion of the surface of the first covering layer, the second covering layer covers at least a portion of the surface of the first covering layer, and the second covering layer contains Ru element.

[0049] In some embodiments, step (1) comprises: synthesizing a solution containing Au particles using a seed-mediated method;

[0050] In some embodiments, step (2) includes: first adding HAuCl4 to the solution in the previous step to react, and then adding H2PdCl4 to react to form a Pd coating layer on the gold particles to obtain Au@Pd particles;

[0051] In some embodiments, step (3) comprises: reacting Au@Pd particles with RuCl3 to obtain a product.

[0052] In a third aspect, the present application provides a hydrogen oxidation reaction catalyst, comprising the composite described in any one of the above items.

[0053] In a fourth aspect, the present application provides a hydrogen fuel cell comprising any of the above-mentioned composites. Preferably, the hydrogen fuel cell is an anion exchange membrane battery.

[0054] In a fifth aspect, the present application provides a method for catalyzing a hydrogen oxidation reaction, comprising contacting a reactant of the hydrogen oxidation reaction with any of the composites described above.

[0055] The complex of the present invention can be widely used as a hydrogen oxidation catalyst in all technical fields requiring hydrogen oxidation. In some embodiments, the hydrogen oxidation reaction is, for example, a hydrogenation reaction in organic catalysis. In some embodiments, the hydrogen oxidation reaction is a Fischer-Tropsch synthesis reaction. In some embodiments, application examples of the hydrogen oxidation catalyst of the present invention include anode catalysts of fuel cells using hydrogen as fuel and anode catalysts of redox flow batteries, particularly in redox flow batteries.

[0056] In some embodiments, in a hydrogen fuel cell, hydrogen and air are reactants, and water is the main byproduct. During the operation of the battery, hydrogen is oxidized at the anode under the action of a catalyst to produce hydrogen ions (protons) and electrons. The former is transported to the cathode through a proton-conducting polymer electrolyte, while the latter is transported to the cathode through an external circuit, thereby providing useful electricity. The oxidation reaction of hydrogen at the anode is called a hydrogen oxidation reaction (HOR), and the catalyst that can catalyze the reaction is a hydrogen oxidation catalyst (HOR catalyst).

[0057] Beneficial Effects

[0058] One or more solutions of the present disclosure have one or more of the following beneficial effects:

[0059] 1) The composite disclosed in the present invention exhibits enhanced catalytic activity as a HOR catalyst, especially maintaining a high catalytic activity at high potential;

[0060] 2) The composite disclosed in the present invention utilizes the hydrogen storage capacity of the first coating layer (such as the Pd layer) and creatively embeds the hydrogen adsorption site, thereby solving the problem that Ru is easily absorbed by oxygen-containing species (OH) in the HOR potential range. ad , O ad etc.) poisoning, causing it to become unusable.

[0061] 3) The composite disclosed in the present invention utilizes the "lattice mismatch" mechanism to form tensile stress in the first coating layer (such as the Pd layer), and the stretched Pd layer exhibits improved storage / release performance;

[0062] 4) The catalytic activity of the composite disclosed in the present invention is negatively correlated with the thickness of the first coating layer (such as the Pd layer). A thinner Pd layer is conducive to the storage and release of activated hydrogen atoms, effectively reducing the energy barrier of the Volmer step that determines the reaction rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1(a) shows Au@Pd x @Schematic diagram of the structure of the Ru complex; Figure 1 (b) shows Au@Pd x Schematic diagram of the lattice mismatch of @Ru complex; Figure 1 (c) shows Au@Pd x Schematic diagram of the Volmer step pathway of the @Ru complex.

[0064] Figure 2 (a) shows Au@Pd 1.1 Low-magnification dark-field transmission electron microscopy (TEM) image of the @Ru complex. Figure 2 (b) shows Au@Pd x High-angle annular dark field scanning TEM (HAADF-STEM) image of @Ru complex, Figure 2 (c), (d) and (e) show the corresponding energy dispersive X-ray (EDX) images of Au, Pd and Ru, respectively.

[0065] Figure 3 (a) shows the Au@Pd 1.1 @Ru's EDX line scan, Figure 3 (b), (c) and (d) show the concentration distributions of Ru, Pd and Au elements respectively.

[0066] Figure 4 (a) shows the Au@Pd 1.1 HAADF-STEM image of @Ru (same as above) complex; (b) (c) (d) show the EDS elemental mapping of Au, Pd and Ru elements; (e) shows the overlay of the image and the elemental mapping.

[0067] Figure 5 (a) shows the HOR polarization curves of each catalyst normalized to the geometric area. Figure 5 (b) shows Au@Pd x @The exchange current density J0 bar graph of the Ru complex.

[0068] Figure 6 (a) shows Au@Pd 1.1 @Raman spectra of Ru at different potentials from 35mV to 785mV. Figure 6 (b) shows the Au@Pd in ​​the deuterium isotope experiment 1.1 @Ru Raman spectra at different potentials from 35mV to 785mV, Figure 6 (c) and (d) show Au@Pd 3.5 @Ru and Au@Pd 6.3 @Ru Raman spectra at different potentials.

[0069] Figure 7 (a), (b), and (c) show the Au@Pd 1.1 @Ru、Au@Pd 3.5 @Ru and Au@Pd 6.3 @Ru complex at different potentials, current density, OH ad Normalized Raman intensity (RI) of bonds and RuO2.

[0070] Figure 8 (a) shows Au@Pd x XPS spectra of @Ru composite and Pd nanoparticles (NPs) in the Pd 3d region. Figure 8 (b) shows Au@Pd x XPS spectra of @Ru composites and Ru nanoparticles (NPs) in the Ru 3d region. DETAILED DESCRIPTION

[0071] The embodiments of the present disclosure will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific conditions are not specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. Where the manufacturers of the reagents or instruments used are not specified, they are all conventional products that can be obtained commercially.

[0072] 1. Preparation of materials

[0073] 1.1Au@Pd x Preparation of @Ru complex

[0074] A series of Au@Pd with different Pd layer thicknesses were successfully synthesized using a seed-mediated method. x @Ru complex, the specific steps are as follows:

[0075] (1) Synthesis of gold nanoparticles

[0076] First, add 3.75 mL of hexadecyltrimethylammonium bromide (0.2 M) solution, 6 mL of water, and 0.25 mL of HAuCl4 (10 mM) solution to a 25 mL colorimetric tube, stir at 30 ° C for 10 minutes, then quickly add 0.6 mL of NaBH4 (0.2 M) solution and react for three hours. Take 2 mL of the above solution into a 200 mL volumetric flask, then add water to make up to volume as the seed solution.

[0077] Add 2 mL of hexadecyltrimethylammonium bromide (0.2M) solution, 0.1 mL of HAuCl4 (10 mM) solution, and then add 20 mL of water, and then add 1.5 mL of ascorbic acid (0.2M) solution. Observe that the color of the solution changes from yellow to colorless and transparent, and then add water to the scale line. Add 0.3 mL of the above seed solution to the colorimetric tube, and observe that the color of the solution changes from colorless to purple-red after 20 minutes, proving that gold nanoparticles have formed in the solution.

[0078] (2) Formation of Pd coating layer

[0079] Add 0.8 mL of HAuCl4 (10 mM) solution to the solution in the previous step, shake well and place in a 30°C environment for reaction. After reacting for 20 minutes, add 0.08 mL-1.0 mL of H2PdCl4 (10 mM) solution and react for 30 minutes to form a Pd coating layer on the gold nanoparticles.

[0080] (3) Formation of Ru coating layer

[0081] The product of the previous step was separated, washed with water and ethanol, dispersed in a 50 mL round-bottom flask, and then 50 mg of ascorbic acid (AA) and 100 mg of polyvinyl pyrrolidone (PVP) were added. Then, it was placed in a 200 ° C oil bath and stirred for 10 minutes. Then, 200 μL of RuCl3 (10 mM) solution was added and reacted for one hour. Finally, the solid-liquid separation was performed to obtain the product Au@Pd x @Ru complex.

[0082] Based on the above synthesis scheme, the amount of H2PdCl4 solution used in step (2) of Example 1 was 0.08 mL, and Au@Pd 1.1 @Ru complex, wherein the surface of Au nanoparticles is coated with a first coating layer (Pd layer) and a second coating layer (Ru layer) in sequence. The particle size of the Au nanoparticles is 50nm, the thickness of the Pd layer is 1.1nm, the thickness of the Ru layer is 0.6nm, and the particle size of the complex is 51.7nm.

[0083] Based on the above synthesis scheme, the amount of H2PdCl4 solution used in step (2) of Example 2 was 0.5 mL, and Au@Pd 3.5 @Ru complex, wherein the surface of the Au nanoparticles is sequentially coated with a first coating layer (Pd layer) and a second coating layer (Ru layer). The particle size of the Au nanoparticles is 50 nm, the thickness of the Pd layer is 3.5 nm, the thickness of the Ru layer is 0.6 nm, and the particle size of the complex is 53.6 nm.

[0084] Based on the above synthesis scheme, the amount of H2PdCl4 solution used in step (2) of Example 3 was 1.0 mL, and Au@Pd 6.3 @Ru complex, wherein the surface of the Au nanoparticles is sequentially coated with a first coating layer (Pd layer) and a second coating layer (Ru layer). The particle size of the Au nanoparticles is 50 nm, the thickness of the Pd layer is 6.3 nm, the thickness of the Ru layer is 0.6 nm, and the particle size of the complex is 56.9 nm.

[0085] 1.2 Preparation of Au@Ru composite

[0086] (1) Synthesis of gold nanoparticles (same method as 1.1)

[0087] (2) Formation of Ru coating layer

[0088] The gold nanoparticles were washed with water and ethanol, dispersed in a 50 mL round-bottom flask, and then 50 mg ascorbic acid (AA) and 100 mg polyvinyl pyrrolidone (PVP) were added. Then, the mixture was placed in a 200 °C oil bath and stirred for 10 minutes. Then, 200 μL of ruthenium trichloride (10 mM) solution was added and reacted for one hour. Finally, the solid-liquid separation was performed to obtain the product Au@Ru nanoparticles.

[0089] The particle size of Au nanoparticles is 50 nm, and the thickness of the Ru layer is 0.6 nm.

[0090] 1.3Ru / C complex

[0091] The Ru content in the Ru / C catalyst is 20 wt%.

[0092] 2. Results and Discussion

[0093] 2.1 Analysis of synthesis mechanism and reaction mechanism

[0094] Figure 1 (a) shows Au@Pd x Schematic diagram of the structure of Au@Pd@Ru complex. x @Ru is a composite particle with a core-shell structure. The composite includes: a substrate 10 (core composed of metal Au); a first coating layer 21 (a first shell composed of metal Pd) and a second coating layer 22 (a second shell composed of metal Ru). The first coating layer 21 coats the substrate 10, and the second coating layer 22 coats the first coating layer 21. General formula Au@Pd x The subscript x of Pd in ​​@Ru represents the thickness of the Pd layer in nm.

[0095] Figure 1 (b) shows Au@Pd x Schematic diagram of the lattice mismatch of the Ru complex. The metal radius of the Au atom in the matrix 10 is The metal radius of the Pd atom in the first cladding layer 21 is The metal radius of the Ru atom in the second coating layer 22 is Since the metal radius of Au atoms is larger than that of Pd atoms, the first coating layer 21 (Pd layer) is subjected to tensile stress (F). The present application found that the tensile stress on the Pd layer is conducive to the entry and exit of activated hydrogen, which plays a positive role in improving the kinetics of the HOR reaction. Figure 1 It can also be seen from (b) that the closer the Pd atoms are to the substrate 10, the more significantly they are affected by the tensile stress, and vice versa. In other words, the thinner the first coating layer 21 (Pd layer), the more significantly it is affected by the tensile stress. The more significantly the first coating layer 21 is stretched, the larger its interplanar spacing is, which is more conducive to the entry and exit of activated hydrogen.

[0096] Figure 1 (c) shows the Au@Pd x Schematic diagram of the Volmer step path of the @Ru complex in the HOR reaction. As shown in the figure: the activated hydrogen (hydrogen atoms) spontaneously overflows from the first coating layer 21 (Pd layer), and the overflowed activated hydrogen (hydrogen atoms) reacts with the OH adsorbed on the second coating layer 22 (Ru layer). ad In the above process, even if the Ru layer is covered with oxygen-containing species (OH ad ) occupied active sites, and can still complete the Volmer step alone. The above process strategically solves the problem that Ru is easily occupied by oxygen-containing species (OH ad ) is poisoned and lacks activity.

[0097] 2.2 Structural characterization

[0098] Figure 2 (a) shows Au@Pd 1.1 Low-magnification dark-field transmission electron microscopy (TEM) image of the Au@Pd@Ru composite. The results show that the final synthesized x @The particle size of the Ru complex is about 50nm. Figure 2 (b) shows Au@Pd x High-angle annular dark field scanning TEM (HAADF-STEM) image of @Ru complex, Figure 2 (c)(d)(e) show the corresponding energy dispersive X-ray (EDX) images of Au, Pd and Ru, respectively. The merged image of Au, Pd and Ru signals shows the clear separation of the three elements, with Au mainly located in the core and Pd and Ru located in the shell.

[0099] Figure 3 (a) shows the Au@Pd 1.1@Ru's EDX line scan image, Figure 3 (b), (c), and (d) show the concentration distribution of Ru, Pd, and Au, respectively. 1.1 @The element distribution of Ru particles from the inside to the surface is Au→Pd→Ru.

[0100] Atomic-resolution elemental mapping was performed using aberration-corrected STEM equipped with an advanced EDS system. Figure 4 (a) shows the Au@Pd 1.1 HAADF-STEM image of Au@Pd@Ru complex; (b) (c) (d) show the EDS elemental mapping of Au, Pd and Ru; (e) shows the superposition of the image and the elemental mapping. The results show that about 3 atomic layers of Pd (thickness 1.1nm) grow on Au atoms; the outermost layer is only Ru atoms and no Au and Pd atoms are observed. The above results show that Au@Pd 1.1 @The Ru complex has an outermost layer of Ru that does not form an alloy with Pd, and the Au core, Pd coating layer, and Ru coating layer have a multilayer core-shell structure in which the phases are separated from each other.

[0101] 2.2 Catalyst activity analysis

[0102] The above-mentioned composite was used as a catalyst and its HOR catalytic performance was tested in a 0.1 M KOH electrolyte (saturated with H2) using a three-electrode system.

[0103] The composite was prepared into a test electrode in the following manner: carbon black and the composite were mixed in isopropanol to form a slurry, which was then evenly coated on a glassy carbon electrode (electrode area 0.197 cm 2 ).

[0104] Figure 5 (a) shows the HOR polarization curve of each catalyst normalized to the geometric area. As shown in the figure, the relationship between the current density j and the potential E of each catalyst is as follows:

[0105] Table 1

[0106]

[0107] As shown above, the three Au@Pd x The catalytic performance of the Au@Pd@Ru complex as a HOR catalyst is significantly better than that of the Au@Ru complex (Comparative Example 1) and the Ru catalyst. x The Au@Pd@Ru complex is active as a HOR catalyst at a high potential of 0.7 V, especially Au@Pd 1.1@Ru material current density can be maintained at 2mA / cm 2 The significantly improved current density is far beyond the expectations of those skilled in the art and is an unexpected technical effect. The catalytic activity test results show that the presence of the Pd layer plays an important role in improving the catalytic activity of Ru and maintaining the high potential oxidation current.

[0108] Figure 5 (b) shows Au@Pd x The exchange current density j0 of the Au@Pd@Ru complex is calculated based on the Butler-Volmer equation j0=jRT / ηF. Where R is the ideal gas constant, T is the temperature, η is the activation overpotential, F is the Faraday constant, and j is the measured current density. The results show that Au@Pd@Ru complex has a 1.1 @Ru、Au@Pd 3.5 @Ru and Au@Pd 6.3 @Ru exchange current density J0 is 2.5mA / cm 2 , 1.3mA / cm 2 and 1.0mA / cm 2 .

[0109] According to the catalytic activity, Au@Pd 1.1 @Ru>Au@Pd 3.5 @Ru>Au@Pd 6.3 @Ru, it can be inferred that the lower the thickness of the Pd layer, the x The catalytic activity of the @Ru complex is higher. The reason for this phenomenon may be that the thinner the Pd layer is, the greater the degree of stretching it is subjected to by the substrate (Au), and a larger degree of stretching is conducive to the entry and exit of activated hydrogen.

[0110] 2.3 In situ Raman testing

[0111] The HOR rate-determining step Volmer process contains the key reactant OH ad and H ad First, the present application uses in situ electrochemical SERS to analyze the OH species in the HOR process of the three catalysts. ad During the test, the slurry containing the composite was coated on a glassy carbon electrode for testing.

[0112] Figure 6 (a) shows Au@Pd 1.1 @Ru Raman spectra at different potentials from 35mV to 785mV. At the starting potential of 35mV, at 615cm -1 and 719cm -1 Two obvious peaks were observed at Figure 6 The species observed in (a) were verified by deuterium isotope experiments. Figure 6 (b) shows the Au@Pd in ​​the deuterium isotope experiment 1.1 @Ru Raman spectra at different potentials from 35mV to 785mV, at 615cm -1 The vibration frequency of the peak at 719 cm remains unchanged, while -1 The vibration frequency of the peak shifted to a lower frequency of 673 cm -1 Therefore, 719cm -1 The species corresponding to the peak is OH ad Species.

[0113] Figure 6 (c) and (d) show Au@Pd 3.5 @Ru and Au@Pd 6.3 @Ru Raman spectra at different potentials. Comparison Figure 6 From (a) to (c), we can see that at the same potential, as the thickness of the Pd layer decreases, the OH ad The vibration frequency of the Raman peak showed an obvious blue shift from 711 cm -1 (Au@Pd 6.3 @Ru) to 714cm -1 (Au@Pd 3.5 @Ru) to 719cm -1 (Au@Pd 1.1 @Ru). This indicates that as the thickness of the Pd layer decreases, the OH ad The adsorption energy with Ru atoms on the catalyst surface gradually increases.

[0114] Figure 7 (a), (b), and (c) show the Au@Pd 1.1 @Ru、Au@Pd 3.5 @Ru and Au@Pd 6.3 @Ru complex at different potentials, current density, OH ad The normalized Raman intensity (RI) of the bond and RuO2. In the potential range of 35mV-135mV, OH ad The peak intensity gradually increases and reaches a maximum value at 135mV. After that, from 135mV to 785mV, OH ad The peak intensity gradually decreased. At the same time, it was also observed that the peak intensity of RuO2 continued to increase.

[0115] 2.4XPS spectral analysis

[0116] Figure 8 (a) shows Au@Pd xXPS spectra of @Ru and Pd complex in the Pd 3d region. Figure 8 (b) shows Au@Pd x XPS spectra of @Ru and Ru complexes in the Ru 3d region.

[0117] like Figure 8 As shown, the decrease in the thickness of the Pd layer leads to the Ru-OH ad The experimental phenomenon of binding energy enhancement can be well explained by the classical d-band center theory. First, Figure 1 As shown in (b), due to lattice mismatch, the second cladding layer 22 (Ru layer) will be subjected to tensile stress from the inner Au lattice, and the smaller the Pd layer thickness, the greater the degree of tension of the Ru layer by the Au lattice, and the greater the strain. Figure 8 (b) XPS characterization revealed that compared with pure Ru, the three Au@Pd x @Ru complex Ru 3d 5 / 2 The binding energy has decreased, indicating that the d-band center has increased. In summary, the strain and electronic effects cause the d-band center of the Ru element to move upward, resulting in the OH on the Ru element ad The adsorption energy is enhanced, which is more conducive to OH ad Stable adsorption of reactants.

[0118] OH ad It is beneficial for the reactants to be stably adsorbed on the Ru element. ad Subsequently, it can react with the activated hydrogen (hydrogen atoms) overflowing from the Pd layer to complete the Volmer step (MH ad +OH - →M+H2O+e - )

[0119] In addition, through Figure 8 (a) XPS characterization found that there is electron transfer between metal Pd and Ru. Pd transfers electrons to Ru, and the electron transfer becomes more obvious as the thickness of Pd decreases. This may also lead to a different electronic structure of Ru and thus affect its performance.

[0120] In summary, this application found that Au@Pd x The Au@Pd@Ru complex can still show particularly high catalytic activity at potentials above 0.7 V (relative to RHE), and the catalytic activity is negatively correlated with the thickness of the Pd layer. x @Ru cleverly uses the hydrogen storage capacity of the inner layer Pd to "temporarily" store the hydrogen enriched at the interface in the low potential range, and then spontaneously overflows in the HOR high potential range and reacts with the OH adsorbed on the Ru layer. ad The above scheme makes it possible to react even if the Ru surface active sites are occupied by OH adThe above scheme strategically solves the problem that Ru is easily occupied by oxygen-containing species (OH ad In addition, the present invention finds that a Pd layer with a smaller thickness is more conducive to OH by precisely controlling the thickness of the Pd layer. ad The stability of the reactants and the storage and release of activated hydrogen are beneficial, thereby effectively reducing the energy barrier of the Volmer step that determines the reaction rate.

[0121] Although the embodiments of the present invention have been described in detail, it will be understood by those skilled in the art that various modifications and changes may be made to the details according to all the teachings disclosed, and these changes are within the scope of protection of the present invention. The full scope of the present invention is given by the attached claims and any equivalents thereof.

Claims

1. A composite comprising: A matrix, wherein the matrix contains a first element, wherein the first element is selected from at least one metal element having a metal radius greater than that of Pd; A first covering layer, wherein the first covering layer covers at least a portion of the surface of the substrate, the first covering layer contains a Pd element, and the thickness of the first covering layer is 1.1 nm-6.3 nm; The second covering layer covers at least a portion of the surface of the first covering layer, and the second covering layer contains a substance having catalytic activity for hydrogen oxidation reaction, and the substance having catalytic activity for hydrogen oxidation reaction is selected from a single substance, an alloy or an intermetallic compound containing Ru.

2. The composite according to claim 1, wherein The thickness of the second covering layer is 0.1 nm-10 nm.

3. The complex according to claim 1, wherein the first element is selected from elements having a metal radius of 1.38 Å or more.

4. The composite according to claim 1, wherein The first element is selected from one or more of Au, Ag, Ti, and Pb.

5. The composite according to claim 1, wherein: The thickness of the second covering layer is 0.5 nm-0.8 nm.

6. The composite according to claim 1, wherein The size of the matrix in at least one dimension is 10 nm to 100 nm.

7. The composite according to claim 1, wherein: The size of the matrix in at least two mutually perpendicular dimensions is 10 nm-100 nm.

8. The composite according to claim 1, wherein: The dimensions of the matrix in three mutually perpendicular dimensions are all between 10 nm and 100 nm.

9. The composite according to claim 1, wherein the composite is a particle having a core-shell structure, wherein the particle comprises a core and a shell covering the core; The core is the matrix; The shell includes a first covering layer and a second covering layer; The first covering layer covers the core; The second covering layer covers the first covering layer.

10. The composite according to claim 1, having one or more of the following characteristics: (1) The first covering layer is epitaxially grown on the substrate; (2) The second cladding layer is epitaxially grown on the first cladding layer.

11. A method for preparing a composite, wherein the composite is as claimed in any one of claims 1 to 10, the method comprising: (1) providing a substrate, wherein the substrate contains a first element, wherein the first element is selected from at least one metal element having a metal radius greater than that of Pd; (2) forming a first covering layer on at least a portion of the surface of the substrate, wherein the first covering layer covers at least a portion of the surface of the substrate, and the first covering layer contains a Pd element; (3) forming a second covering layer on at least a portion of the surface of the first covering layer, wherein the second covering layer covers at least a portion of the surface of the first covering layer, and the second covering layer contains Ru element; Step (1) comprises: synthesizing a solution containing Au particles by a seed-mediated method; Step (2) comprises: first adding HAuCl4 to the solution in the previous step to react, and then adding H2PdCl4 to react to form a Pd coating layer on the gold particles to obtain Au@Pd particles; Step (3) includes: reacting Au@Pd particles with RuCl3 to obtain a product.

12. A hydrogen oxidation reaction catalyst, comprising the composite according to any one of claims 1 to 10.

13. A hydrogen fuel cell comprising the composite according to any one of claims 1 to 10.

14. The hydrogen fuel cell according to claim 13, wherein: The hydrogen fuel cell is an anion exchange membrane fuel cell.

15. A method for catalyzing a hydrogen oxidation reaction, comprising contacting a reactant of the hydrogen oxidation reaction with the composite according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Electrode catalyst, composition for forming gas diffusion electrode, gas diffusion electrode, membrane-electrode assembly, and fuel cell stack

    US20160233519A1